Functional labour market areas for Chile - Francisco Rowe; José Manuel Casado Díaz; Lucas Martínez-Bernabéu (REGION, 2017)
Administrative areas are arbitrarily designed and do not necessarily reflect the geographical patterns of socio-economic and labour market activity. Labour market areas (LMAs) are required to analyse spatial labour market activity and provide a framework to guide spatially-explicit employment policy development. This resource describes a data source of a set of recently created labour market areas for Chile.
Keywords: 330; Spatial labour markets; Labour; Evolutionary